2014
DOI: 10.1016/j.neuroimage.2014.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Investigating brain connectivity heritability in a twin study using diffusion imaging data

Abstract: Heritability of brain anatomical connectivity has been studied with diffusion-weighted imaging (DWI) mainly by modeling each voxel's diffusion pattern as a tensor (e.g., to compute fractional anisotropy), but this method cannot accurately represent the many crossing connections present in the brain. We hypothesized that different brain networks (i.e., their component fibers) might have different heritability and we investigated brain connectivity using High Angular Resolution Diffusion Imaging (HARDI) in a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 101 publications
6
40
0
Order By: Relevance
“…As illustrated in our analysis of twins, the similarity in monozygotic twins was around twice as much of the dizygotic twins, whereas our post-hoc analysis did not find significant similarity difference between dizygotic twins and non-twins siblings. These results are highly suggestive that genetics contribute a substantial portion to the overall construction of the local connectome, which is consistent with previous studies showing high heritability in cortical connections [30, 31] and white matter integrity [3235]. Nevertheless, our results also showed that the monozygotic twins shared only 12.51% similarity in local white matter architecture.…”
Section: Discussionsupporting
confidence: 92%
“…As illustrated in our analysis of twins, the similarity in monozygotic twins was around twice as much of the dizygotic twins, whereas our post-hoc analysis did not find significant similarity difference between dizygotic twins and non-twins siblings. These results are highly suggestive that genetics contribute a substantial portion to the overall construction of the local connectome, which is consistent with previous studies showing high heritability in cortical connections [30, 31] and white matter integrity [3235]. Nevertheless, our results also showed that the monozygotic twins shared only 12.51% similarity in local white matter architecture.…”
Section: Discussionsupporting
confidence: 92%
“…A large proportion (40-80%) of the intersubject variance in the DTI-FA values(Braskie et al, 2011; Chiang et al, 2012; Chiang et al, 2009; Jahanshad et al, 2012; Jahanshad et al, 2010; Kochunov et al, 2015; Shen et al, 2014) and processing speed measurements(Glahn et al, 2011; Glahn et al, 2013) is explained by additive genetic factors. The high degree of genetic influence of these two traits posits them as important endophenotypes for genetic search for risk factors for heritable psychiatric disorders such as schizophrenia that are associated with both DTI-FA and processing speed deficits.…”
Section: Introductionmentioning
confidence: 99%
“…CN subjects were recruited via print and electronic media, and noticeboards in universities and local communities. Sample ascertainment and separate clinical assessments for younger (15)(16)(17)(18)(19)(20)(21) and older (22)(23)(24)(25)(26)(27)(28)(29)(30) age categories are provided in Perich et al 36 and in Supplementary Information 1.1. We pooled data across both age cohorts unless there was a specific correlation between a brain network measure and an age-specific clinical variable in either group.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…15 Given the strong heritability of WM morphology, 16,17 studying individuals at familial risk of developing BD may help identify neurobiological factors that pre-empt the development of BD, as well as factors associated with resilience. This objective is particularly pertinent in young first-degree relatives who have not yet passed the peak age of illness onset.…”
Section: Introductionmentioning
confidence: 99%